Teneurin paralogues are able to localise synaptic sites driven by the intracellular domain and have the potential to form cis-heterodimers - Cheung, Angela; Schachermayer, Greta; Biehler, Aude; Wallis, Amber; Missaire, Mégane; Hindges, Robert (Frontiers in Neuroscience, 2022)
Synaptic specificity during neurodevelopment is driven by combinatorial interactions between select cell adhesion molecules expressed at the synaptic membrane. These protein-protein interactions are important for instructing the correct connectivity and functionality of the nervous system. Teneurins are one family of synaptic adhesion molecules, highly conserved and widely expressed across interconnected areas during development. These type-II transmembrane glycoproteins are involved in regulating key neurodevelopmental processes during the establishment of neural connectivity. While four teneurin paralogues are found in vertebrates, their subcellular distribution within neurons and interaction between these different paralogues remains largely unexplored. Here we show, through fluorescently tagging teneurin paralogues, that true to their function as synaptic adhesion molecules, all four paralogues are found in a punctate manner and partially localised to synapses when overexpressed in neurons in vitro. Interestingly, each paralogue is differentially distributed across different pre- and post-synaptic sites. In organotypic cultures, tenm3 is similarly localised to dendritic spines in CA1 neurons, particularly to spine attachment points. Furthermore, we show that the intracellular domain of teneurin plays an important role for synaptic localisation. Finally, while previous studies have shown that the extracellular domain of teneurins allows for active dimer formation and transsynaptic interactions, we find that all paralogues are able to form the full complement of homodimers and cis-heterodimers. This suggests that the combinatorial power to generate distinct molecular teneurin complexes underlying synaptic specificity is even higher than previously thought. The emerging link between teneurin with cancers and neurological disorders only serves to emphasize the importance of further elucidating the molecular mechanisms of teneurin function and their relation to human health and disease.